Analisis Dampak Penerapan Milk District Model Nestle Terhadap Aksesibilitas Livelihood Assets Peternak Sapi Perah di Jawa Timur (Studi pada Empat Wilayah Penampungan Susu Segar) - B.A. Nugroho; P.S. Winarto (Universitas Andalas, 2011)
East Java province is one of the development centre of dairy farming in Indonesia. In 2008, dairy farming activities in East Java constitue is about 88,148 dairy farmers, 29 dairy cooperatives, 130,000 dairy cows, and produces 600,000 litres freshmilk per day, from that amount 410,000 litres marketed to PT. Nestle. This study was conducted to analysis macro impact of milk district model Nestle on 1) labor absorption, natural resources conservation, and regional economic growth and 2) on capital assets accessibility of dairy farmers. Analysis methods that we used in this study were 1) field survey using questionnaire; 2) collecting secondary data; 3) in depth interview using checklist; and 4) measuring accesssibility on livelihood assets (human, natural, physics, social and financial accesss). Areas of study located on three regencies in East Java Province: Malang, Blitar and Kediri, 97 smallscale dairy farmers were surveyed. The impacts of milk district model on livelihood assets accessibilities remain significants especially on financial and social capitals. This means that dairy farmers accesssibilities on financial sources were improved because it provide regular source of income, something the dairy farmers would not receive from their seasonal crops. Accessibility level of social capital were improved too, this means that smallscale dairy farming activities capables to create many collective activities on the rural communities based on dairy farming issues through variety efforts on Artificial Insemination (AI), feeding process, freshmilk handling, freshmilk collecting, forages management, breeding, animal healthcares, etc. Accessibility level on human, physical and natural capitals remainds lower than social and financial capitals because there are a lack of human capital (knowledge, skills, creativity and adaptive strategy); a lack of physical capital (rural infrastructures); and natural capital (clean water availability).